Pengaruh Produk Domestik Bruto (PDRB), Upah Minimum Kota/ Kabupaten (UMK), dan Indeks Perkembangan Manusia (IPM) Terhadap Penyerapan Tenaga Kerja di Provinsi Jawa Tengah Tahun 2016-2019 - Eka Putri; Eni Setyowati; Imron Rosyadi (Ekonomis: Journal of Economics and Business, 2022)
Absorption of labor is one of the most important things that can affect economic development in an area. Problems in employment are complex and influenced by many factors. This study aims to determine the effect of Gross Domestic Product (GRDP), City Minimum Wage (UMK), and Human Development Index (IPM) on employment in several cities in Central Java. This research uses panel data analysis with Fixed Effect Model (FEM) method. The results of data processing, showed that the MSE had a significant positive effect on employment. Meanwhile, GRDP does not significantly affect employment. The HDI variable has no significant effect on employment.